Preparação e caracterização da casca de banana prata particulada para aplicação com reforço em compósito de matriz de PEAD - Watashi, Cíntia Yumi [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The waste, exaggerated and incorrect disposal of biomass are common practices in modern times where everything is disposable. However the growing concern with the nature and the environment compel man to give nobler destinations for these products through sustainability and recycling of waste. Banana peel is a residual biomass, which is not consumed. It generates tons of waste per week in São Paulo city. This trash is disposed in dumps and landfills, which could be reduced by using it as reinforcement in natural composites. The high density polyethylene (HDPE) is a polymer derived from the ethylene polymerization and is easily recycled. Which makes it a sustainable material. In the present work characteristics of the natural composite composed with banana peel and high-density polyethylene were studied. It was noted that removing the lignin present in the banana peel, the fiber introduces a significant improvement in thermal resistance. The preparation of composite was made with a ratio of 5% and 10% of reinforcement in comparison with polymeric matrix mass. Composites were thermally, mechanically and microscopically characterized. The addition of fiber in the polymer increased the mechanical strength of the composite. The fiber surface treatment with distilled water removed the amorphous material present in the fibers, improving significantly thermal stability and increasing crystallinity of the celullose. The addition of 5% fiber in mass to the polymer increased significantly the tensile strength and elasticity modulus for the composite. With 10% of fiber addiction there were also an improvement when compared with pure HDPE, but when compared with 5% composite the mechanical properties are slightly lower. This may be due to the fiber particle size, which are small and eventually become a hub of tension ... (Complete abstract click electronic access below)

O desperdício, descarte exacerbado e incorreto de biomassas residuais são práticas comuns nos tempos modernos em que tudo se torna descartável. Porém, a crescente preocupação com a natureza e com o meio ambiente, leva o homem a destinar aplicações mais nobres a esses produtos, o que contribui para a sustentabilidade e a reciclagem desses resíduos. A casca da banana é uma biomassa residual, a qual não é consumida e acaba gerando toneladas de detritos. Por exemplo, a cidade de São Paulo, produz 4 toneladas de casca de banana por semana, a qual são descartadas em lixões e depósitos de lixo. No entanto esses detritos poderiam ser reduzidos através da utilização dos mesmos como reforços em compósitos naturais. O polietileno de alta densidade (PEAD) é um polímero derivado da polimerização do etileno e é facilmente reciclado. O que o torna um material sustentável. No presente trabalho foi estudado o compósito natural composto pela casca da banana e o polietileno de alta densidade. As fibras foram tratadas com o intuído de remover o material amorfo e diferentes proporções de fibra foram adicionadas ao polímero puro. No preparo dos compósitos foram utilizadas as proporções de 5% e 10% de reforço em relação à massa de matriz poliméria. Os compósitos foram caracterizados: térmica, mecanicamente e microscopicamente. O tratamento com H2Odestilada na fibra removeu parte do material amorfo presente na celulose, melhorando significativamente sua estabilidade térmica e aumentando a cristalinidade da fibra. A adição de 5% de fibra no polímero aumentou consideravelmente a resistência à tração e o módulo de elasticidade no compósito. Com a adição de 10% o compósito apresentou melhoras em relação ao PEAD puro, porém em relação ao compósito de 5% apresentou leve diminuição das propriedades mecânicas. Tal fato ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Compositos polimericos; Materiais compostos; Polietileno; Fibras; Natural composite; Banana peel; High density polyethylene